Approach and management of checkpoint inhibitor-related immune hepatitis - Sanjeevaiah, Aravind (J Gastrointest Oncol, 2018)
Immune checkpoint inhibitors have promising clinical activity across multiple gastrointestinal cancers and immune-mediated hepatotoxicity is particularly relevant for this group of patients. In this article we will review the recognition, workup and management of suspected checkpoint inhibitor related immune-hepatitis.